KEBERHASILAN PROGRAM SUBSIDI KESEHATAN TERHADAP ALOKASI BIAYA KESEHATAN KELUARGA MISKIN: STUDI PADA PENERIMA BANTUAN IURAN DI NGAMPRAH, KABUPATEN BANDUNG BARAT - Neni Murniati; Risky Mei Rimbani; Ulfah Mawaddah (Universitas Pasundan, 2021)
One of the many determinants of the level of welfare can be measured by the level of health. Many countries in the world are working to improve the health of their citizens in order to promote the welfare of the country itself. Not to forget, Indonesia is also one of the countries that implements health improvement programs in the community. The health subsidy program is one form of implementation of the focus of attention of the Indonesian government in supporting national health, so that finally this program has been implemented to the lowest level in Indonesia. This study aims to explore the progress of the program so that it can be considered successful in reducing the health costs of poor families. This research was conducted using quantitative data analysis methods. The data concerned, sourced from secondary data obtained from (BPA3AKB) West Bandung Regency, Ngamprah District, and also involved primary data obtained from the implementation of field surveys. The case study sample was obtained from the community who received contribution assistance in Ngamprah District, West Bandung Regency, using a sample size of Slovin and cluster random sampling techniques. The results of data processing in the end show that the PBI program provided by the Government to the poor has been observed to be able to reduce average household expenses to be transferred to health costs. Moreover, there were a number of changes in consumption patterns in the community before and after the program was implemented.